EFEKTIVITAS MEDIA SPINNING WHEEL TERHADAP KETERAMPILAN MEMBACA SUKU KATA DIAGRAF NY PADA SISWA DISABILITAS INTELEKTUAL RINGAN - Bunga Sukma Wati; Taufan Johandri; Nurhastuti; Nasri Yosa Yulia (Jurusan Pendidikan Bahasa dan Seni Fakultas Keguruan dan Ilmu Pendidikan Universitas Lampung, 2026)
Early reading skills are an important basic skill for students, including those with mild intellectual disabilities. However, students with this condition often have difficulty combining letters into the correct sounds, especially in words containing the diagraph